Standard Operating Procedure (SOP) for developing irrigation scheduling - Raes, D.; Shrestha, Nirman (International Water Management Institute (IWMI). CGIAR Initiative on Excellence in Agronomy, 2024)
This Standard Operating Procedure (SOP) for Developing Irrigation Scheduling provides a step-by step guidance to develop farmer-led irrigation schedules tailored for specific crops, soil types, and climatic conditions. The document covers graphical approaches and the use of FAO’s AquaCrop model to develop irrigation schedules tailored to different cropping systems, including conventional and micro-irrigation techniques. By integrating real-time and historical weather data, it ensures water-efficient agricultural practices, improving productivity and resilience to climate variability. The SOP was designed for agronomists interested e.g. in supplementary irrigation.